PROVIDER'S RESPONSIBILITY FOR DATA PERSONAL CONSUMER ASSOCIATED WITH PRIME CARD REGISTRATION - Anugrah Prima Utama (Indonesia Private Law Review, 2023)
To minimize starter packs, the Government, through Regulation of the Minister of Communication and Information Number 12 of 2016 jo. Regulation of the Minister of Communication and Informatics Number 14 of 2017 concerning the Registration of Telecommunications Service Customers requires consumers to send personal data to the operator as a National Identity Number and Family Card Number or biological mother's name. However, this condition needs to be addressed appropriately, bearing in mind that the use of personal data by irresponsible parties without approval or authorization or because electronic system failures are prone to occur. The problems in this research are further examining the legal relationship between the provider and the consumer, the provider's responsibility to the consumer's data regarding starter pack registration, and the legal remedies consumers can take when personal data protection fails. The method used in this research is normative, carried out by reviewing existing laws and regulations and the literature related to the research topic. This study's results indicate a legal relationship between providers and consumers marked by registration recruitment. The provider, in this case, is the party that formulates the agreement, while the consumer only agrees and follows the agreed terms. Furthermore, the operator has responsibility for the telecommunications services it provides, including maintaining legitimacy, truth, accuracy, and relevance, as well as suitability to obtain, collect, analyzing, process, display, store, post, send, disseminate, to destroying personal data by the provisions legislation. And suppose there is a failure to protect the confidentiality of personal data. In that case, consumers can file legal remedies through complaints, civil lawsuits through court and alternative dispute resolution, or prosecution of providers.